Kearifan Lokal Sekolah Sebagai Basis Pengembangan Program Bimbingan Dan Konseling Komprehensif - eko perianto (STKIP Andi Matappa, 2018)
The development of guidance and counseling programs, especially those planned (planned) and implemented (actuating) by guidance and counseling teachers will impact on how the provision of services to learners (counselee). Therefore a good program will show how the existence of teacher guidance and counseling in the field. Comprehensive guidance and counseling programs are comprehensive. Guidance and counseling activities are a series of activities that are related, connected, and each part has a unity bond with another part that is oriented towards the achievement of certain goals. Comprehensive guidance and counseling programs based on local school wisdom can be realized in several ways (1) Identify the needs of learners by developing data instruments based on school culture values. (2) engaging in school-oriented guidance and counseling services and (4) involving all stakeholders to provide counseling and guidance services based on local school wisdom.